Legal Certainty on Impeachment of the President and/or Vice President Judging from the 1945 Constitution - H. Muhamad Rezky Pahlawan MP (East Asian Journal of Multidisciplinary Research, 2022)
A state official's removal from office requires well-defined terms about the official's legal standing. The President of Indonesia has a pivotal role in any presidential system as the country's Head of State and Head of Government. To clarify the process for the dismissal of the President and/or Vice President, Articles 7A, 7B, 7C, and Article 8 were added to the 1945 Constitution. The MPR will conduct the impeachment procedure by a vote. There will be a negative impression of the procedure for removing the President and/or Vice President as a result of this. Verdicts from the Criminal Court on alleged breaches of the Criminal Law need either the affirmation of the Constitutional Court's authority or the passage of time.